DEVELOPMENT AND APPLICATION OF MULTIPLEX PCR FOR THE DETECTION OF ESCHERICHIA COLI AND VIBRIO CHOLERAE IN STREET FOODS - Tien, Nguyen; Lam, Nguyen; Kha, Hoang; Loc, Nguyen (Food and Feed Research, 2026)
PCR is a very useful method for detecting the presence of pathogenic microorganisms in foods and organisms. This study developed a multiplex PCR (mPCR) method for detecting E. coli and V. cholerae in some street foods in Dong Ha, Vietnam, through the housekeeping genes phoA and sodB, respectively. This study used methods such as single PCR, multiplex PCR, and bacterial culture. The study established appropriate mPCR conditions to detect E. coli and V. cholerae at a minimum concentration of 101 CFU/mL and 102 CFU/mL, respectively. The developed mPCR method successfully detected E. coli in 93.75% of the street food samples, including nem chua, tôm chua, and bún hến, whereas Vibrio cholerae was not detected in any of the tested samples.